Latin American migrants under the US New Political Economy: Public raids cost vs private sanctuary revival - Antonio Sánchez-Bayón (América Latina en la Historia Económica)
This is a case study on migration management in the United States of America, according to the New Political Economy approach. Attention is paid to how Latin American immigrants are treated, given the change in public policies and their economic perception. There has been a shift from open-door immigration policies to raids and massive deportations, violating the founding principles of the United States and the key to its growth and development, since immigrants are not only a greater productive factor of work, but also bring knowledge, technologies and institutions that improve the competitiveness. Faced with this change in public powers, civil society has reacted, with a revitalization of the Sanctuary Movement. This study uses an explanatory methodology on the evolution of the academic disciplines and approaches dedicated to the research on religion-economics-migration relations, to focus its attention on the case study of the Sanctuary Movement.